2020
DOI: 10.1021/acsphotonics.0c00363
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Colloidal Quantum Dot Infrared Photodiode

Abstract: Lead sulfide (PbS) colloidal quantum dots (QDs) have received attentions as materials for near-infrared (NIR) photodetection in view of their strong and tunable absorption in the NIR region and room-temperature solution processability. However, the realization of high-speed PbS QD photodetection has been severely hindered by the extremely low carrier mobility (∼10 −5 to 10 −2 cm 2 V −1 s −1 ). Here, an ultrafast PbS QD photodiode fabricated with low mobility QDs (∼10 −3 cm 2 V −1 s −1 ) is demonstrated, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…Ranging between 0.6 and 1.6 µs, these rise and fall times are comparable to some of the fastest mature PbS QDPDs, for which times of a few µs have been reported. [ 48 , 49 , 50 ]…”
Section: Resultsmentioning
confidence: 99%
“…Ranging between 0.6 and 1.6 µs, these rise and fall times are comparable to some of the fastest mature PbS QDPDs, for which times of a few µs have been reported. [ 48 , 49 , 50 ]…”
Section: Resultsmentioning
confidence: 99%
“…With the well-passivated Si surface, we then proceeded to build Si:CQD heterojunction photodiodes. The PbS CQDs were synthesized via a hot-injection method according to previous reports 38 (also see the Methods section). The absorption spectrum of the PbS CQD in Figure 3a shows an exciton peak at 1290 nm (see Figure S6 for the transmission electron microscopic (TEM) image).…”
Section: Resultsmentioning
confidence: 99%
“…This post-synthetic surface engineering leads to high carrier mobility (4×10 -2 cm 2 V -1 s -1 ) and improved device power conversion efficiency. 2) In 2014, Chuang et al [56] showed different ligands can be gained from the development and characterization of PbS nanocrystals and devices will facilitate their use for example in photodiode applications [164,165] or can be applied to the development of other nanocrystal chemistries for solar cells, such as leadhalide perovskites as well as non-toxic, lead-free nanocrystals such as AgBiS 2 , [166] Cu 2 S, [167] or Cu 3 BiS 3 nanocrystals. [168]…”
Section: Outlook: Realizing Nanocrystal Devicesmentioning
confidence: 99%